Effect of Polypropylene Fibers on Self-Healing and Dynamic Modulus of Elasticity Recovery of Fiber Reinforced Concrete - Adham El-Newihy; Pejman Azarsa; Rishi Gupta; Alireza Biparva (Fibers, 2018)
This study aims to evaluate self-healing properties and recovered dynamic moduli of engineered polypropylene fiber reinforced concrete using non-destructive resonant frequency testing. Two types of polypropylene fibers (0.3% micro and 0.6% macro) and two curing conditions have been investigated: Water curing (at ~25 Celsius) and air curing. The Impact Resonance Method (IRM) has been conducted in both transverse and longitudinal modes on concrete cylinders prior/post crack induction and post healing of cracks. Specimens were pre-cracked at 14 days, obtaining values of crack width in the range of 0.10–0.50 mm. Addition of polypropylene fibers improved the dynamic response of concrete post-cracking by maintaining a fraction of the original resonant frequency and elastic properties. Macro fibers showed better improvement in crack bridging while micro fiber showed a significant recovery of the elastic properties. The results also indicated that air-cured Polypropylene Fiber Reinforced Concrete (PFRC) cylinders produced ~300 Hz lower resonant frequencies when compared to water-cured cylinders. The analyses showed that those specimens with micro fibers exhibited a higher recovery of dynamic elastic moduli.